Предмет: Математика,
автор: 58Dana47
Помогите решить пример (12х+3):(-1.5) при х=-1
Ответы
Автор ответа:
0
Ответ:
(12х + 3):(-1,5) при х = -1
(12х+3):(-1,5) = (12*(-1)+3):(-1,5) = (-12+3):(-1,5) = -9 :(-1,5) = 6
Пошаговое объяснение:
sofia1138:
ну блин ты меня опередил(а)
Автор ответа:
0
Ответ:6
Пошаговое объяснение:
(12*(-1) +3):(-1,5)=(-12+3):(-1,5)=-9:(-1,5)=6
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: анько123
Предмет: Английский язык,
автор: NiCoLiKa
Предмет: Химия,
автор: qwert1520
Предмет: Литература,
автор: этотипомойник